New trends in psychology - Yale, Stanley N. (Kendall / Hunt, 1989)
For many years, both as a psychotherapist and a psychology teacher, [the author] felt the need for supplementary reading material for [his] students, patients, and friends. The readings are condensed samplings of various trends and approaches to the study of psychotherapy and psychology. What follows is a chronicle of [the author's own] journey through, and transformation to, different schools of thought and therapy in the study of psychology and psychiatry. -Pref